Selective Oestrogen Receptor Agonists Rescued Hippocampus Parameters in Male Spontaneously Hypertensive Rats - Pietranera, Luciana (2016)
Spontaneously hypertensive rats (SHR) show pronounced hippocampus alterations, including low brain-derived neurotrophic factor (BDNF) expression, reduced neurogenesis, astrogliosis and increased aromatase expression. These changes are reverted by treatment with 17b-oestradiol. To determine which oestradiol receptor (ER) type is involved in these neuroprotective effects, we used agonists of the ERa [propylpyrazole triol (PPT)] and the ERb [diarylpropionitrite (DPN)] given over 2 weeks to 4-month-old male SHR. Wistar Kyoto normotensive rats served as con trols. Using immunocytochemistry, we determined glial fibrillary protein (GFAP)+ astrocytes in the CA1, CA3 and hilus of the dentate gyrus of the hippocampus, aromatase immunostaining in the hilus, and doublecortin (DCX)+ neuronal progenitors in the inner granular zone of the den tate gyrus. Brain-derived neurotrophic factor mRNA was also measured in the hippocampus by the quantitative polymerase chain reaction. In SHR, PPT had no effect on blood pressure, decreased astrogliosis, slightly increased BDNF mRNA, had no effect on the number of DCX+ progenitors, and increased aromatase staining. Treatment with DPN decreased blood pressure, decreased astrogliosis, increased BDNF mRNA and DCX+ progenitors, and did not modify aro matase staining. We hypothesise that, although both receptor types may participate in the pre viously reported beneficial effects of 17b-oestradiol in SHR, receptor activation with DPN may preferentially facilitate BDNF mRNA expression and neurogenesis. The results of the present study may help in the design of ER-based neuroprotection for the encephalopathy of hyperten sion.